Pengembangan Komik IPAS pada Materi Sistem Pencernaan Manusia untuk Melatih Nature of Science (NOS) Siswa Usia 10-11 Tahun - Peni Yunita; Chairul Amriyah; Antomi Saregar (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This research aims to develop IPAS comics on human digestive system material to train Nature of Science (NOS) for 10-11 year old students. The method used is the Borg and Gall model, involving validators from two media experts, two material experts, and one language expert. The validation results show that the developed comic has high feasibility, with percentages of 94% for material, 97% for media, and 98% for language. Thus, this comic is feasible and can be used as a learning medium, and is expected to increase students' understanding and interest in natural science. This research recommends integrating comics into the curriculum to support more innovative learning.